ANALISIS SWOT SEBAGAI DASAR PERUMUSAN VISI MISI LEMBAGA PENDIDIKAN ISLAM - MIFTAHUL AFKARINA, MIFTAHUL AFKARINA (JURNAL ILMU PENDIDIKAN, 2024)
This research constitutes a literature review study that employs books and other scholarly works as sources of data. The aim of this research is to propose the implementation of SWOT analysis as the foundation for formulating the vision, mission, and objectives of Islamic educational institutions. Based on the findings from previous literature, it is established that the formulation of vision and mission is vital to provide inspiration and motivation for an institution, particularly Islamic educational institutions in this context, to establish a common mindset and objectives for all school members in accordance with the teachings and guidance of Islam. Vision, mission, and objectives are not formulated instantly without a foundation. One of the factors that can underpin the quality of vision and mission is the analysis of the strengths, weaknesses, opportunities, and threats of educational institutions. These four factors influence the success of an endeavor. In order to address internal (Strengths and Weaknesses) and external (Opportunities and Threats) conditions, an analysis is required to generate formulations that align with the demands of societal changes, which can then provide guidance to all members within the organization to work in accordance with the collectively established vision and mission. Internal conditions that play a role in the formulation of vision include the analysis of students, educational personnel, school physical facilities, curriculum analysis, educational materials, and the learning process. In external conditions, educational institutions face factors that also need to be examined to ensure that the vision and mission have a positive impact and can guide all members of the institution to achieve their goals, endure various conditions, and cope with all challenges. To achieve this success, it is necessary to conduct an analysis of the social environment of society, the role of government and foundations, as well as global challenges.